INCLUSÃO EM MOVIMENTO: TRANSFORMAR DESAFIOS EM OPORTUNIDADES - Sara Diana Pereira Alves (2024)
I embarked on a unique adventure to discover the teaching profession. This final report seals my journey as a preservice teacher and opens the door to my future as a teacher. Throughout this voyage, I will navigate the uncharted waters of teaching, exploring new knowledge and uncovering hidden treasures in every experience. I begin by preparing my luggage, taking an introspective look at myself and my initial expectations. I discuss my boat (the school), my passengers (the students), and the crew (my fellow travelers). In the Nautical Chart, I include Planning, Evaluation, and Reflection as fundamental processes for the success of this journey. Along the way, I encountered waves and storms, highlighting the main challenges faced and how I navigated each: heterogeneity versus homogeneity, inclusion, and assessment. The report culminates with the presentation of a research study on a current and vital topic, aimed at identifying pedagogical strategies, curricular adaptations, and teaching approaches that facilitate and enhance the motor, social, and cognitive development of a student with Asperger's Syndrome. This school placement has been an extraordinary adventure, full of challenges and learning. The journey may have ended, but I know that many other seas await me. With my heart full and my compass finely tuned, I feel ready to continue sailing the vast ocean of education, seeking new challenges and opportunities.